Ensaios sobre oferta pública de ações e estabilização de preços - Pinheiro, Douglas Beserra (2014)
In public offerings, whether initial public offerings (IPO) or seasoned public offerings (SEO), whose sale occurs via firm commitment, is common to include a stabilization clause, which allows underwriters repurchase shares on the market after the beginning of negotiations with the aim of delaying or preventing the fall in the value. The repurchased shares are those from the option given by the issuer to the underwriter for the sale in excess of up to 15% of the shares initially offered, in addition, in case of strong demand an additional sale can occur up to the limit of 20% of the initial offering, called hot-issue, but these actions are cannot be repurchased. The green shoe option allows the underwriters buy part or all the shares sold in excess, increasing supply permanently. This thesis evaluates, in this order, the main determinants of stabilization and its effects on short-term return of SEOs, the effects on the cost of issuing shares and then the effect on the long-term return of IPOs and SEOs, each topic is evaluated in a different and independent chapter, after an introductory chapter which describes the structure of the thesis. In the first chapter the results indicate that in SEOs, the risk, liquidity and demand of domestic and foreign institutional investors are important in determining the occurrence of over-allocation and stabilization, and in addition to these factors the demand from retail investors also affect the intensity of stabilization. As for the effects on return immediately after the end of stabilization, the non-stabilized SEOs exhibit short-term return higher than stabilized and, on average, the prices do not fall after the end of stabilization, however, the greater the intensity of the repurchases, the lower are post-stabilization returns. In the second chapter, it was found that underwriters predict the intensity of stabilizing and/or the exercise of the greenshoe and hot-issue options, and since they are paid by the sale of these additional shares, they adjust ex-ante the remuneration charged to issuers, not appropriating of an eventual profit nor bearing the cost of repurchase and return the shares to the issuer. These results were observed both in IPOs and SEOs, moreover, the same effect was observed in the total costs. In the latter chapter has been shown that the level of stabilization and/or exercise of the green shoe and hot-issue does not affect the long-term return of IPOs, however the greenshoe and 9 hot-issue exercise negatively affect the adjusted cumulative returns of SEOs until the 3rd year after the issuance, even when controlling by the issuance size and market-to-book ratio. Some major contributions of this thesis are: 1) despite the difference in the risk level, the results of the occurrence and intensity of stabilization are generally similar to those observed for IPOs, 2) this is the first study to examine the stabilization effects in SEO short-term returns, as well as its finding that the market return influences the intensity of stabilization, 3) for the first time shows that the size of the stabilization process are anticipated by underwriters and in the context of a competitive market, are included into the cost of issuing IPO and SEO, 4) notes that the stabilization process has effect on long-term return of SEOs. All these results cast doubt on studies of return and compensation of public offerings that exclude such information in their models.